2021
DOI: 10.1002/jia2.25774
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SMS and peer navigation on retention in HIV care among adults in South Africa: results of a three‐arm cluster randomized controlled trial

Abstract: Introduction Few interventions have demonstrated improved retention in care for people living with HIV (PLHIV) in sub‐Saharan Africa. We tested the efficacy of two personal support interventions – one using text messaging (SMS‐only) and the second pairing SMS with peer navigation (SMS+PN) – to improve HIV care retention over one year. Methods In a cluster randomized control trial (NCT# 02417233) in North West Province, South Africa, we randomized 17 government clinics to three conditions: SMS‐only (6), SMS+PN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…However, systematic reviews from low-to middle-income countries have found mixed or inconclusive evidence of the impact of SMS text messaging interventions, which are often not explicitly designed using behavior change theory [20][21][22]. In South Africa, SMS text messaging interventions have shown highly promising results for HIV care adherence, support, and education [23][24][25], as well as for pregnant and postpartum women, through the National MomConnect SMS text message health messaging program [26,27]. Data from high-income settings suggest that a 2-way SMS text messaging intervention can support nutritional behavior change, resulting in weight loss and maintenance in the postpartum period [28], and that a mobile app can effectively improve preconception nutrition [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, systematic reviews from low-to middle-income countries have found mixed or inconclusive evidence of the impact of SMS text messaging interventions, which are often not explicitly designed using behavior change theory [20][21][22]. In South Africa, SMS text messaging interventions have shown highly promising results for HIV care adherence, support, and education [23][24][25], as well as for pregnant and postpartum women, through the National MomConnect SMS text message health messaging program [26,27]. Data from high-income settings suggest that a 2-way SMS text messaging intervention can support nutritional behavior change, resulting in weight loss and maintenance in the postpartum period [28], and that a mobile app can effectively improve preconception nutrition [29].…”
Section: Introductionmentioning
confidence: 99%
“…While the pilot was not powered to detect significant differences between the two arms, the point estimates of effect are intended to provide preliminary evidence of impact as well as early indicators of the sample size needed to power a future trial. Based on findings in our previous navigation trial [ 33 , 34 ], we would have needed 328 participants to have sufficient power to detect an equivalent effect (OR 1.78) of the intervention on retention.…”
Section: Methodsmentioning
confidence: 99%
“…To address this, we developed a trans-specific peer-based patient navigation (PN) intervention for the Brazilian context to address social, structural, and personal barriers to care. The intervention utilized elements of a successful peer-based program with trans women in the US [ 30 , 31 ] and a PN study conducted in South Africa [ 32 ] with cisgender adults that improved retention in care [ 33 , 34 ]. We examine feasibility and acceptability of the “Trans Amigas” intervention and explore initial efficacy among 113 TWH in São Paulo, Brazil who participated in a randomized controlled pilot trial to increase engagement in HIV care.…”
Section: Introductionmentioning
confidence: 99%
“…This secondary analysis is based on the I-Care study, conducted in the Bojanala Platinum District of North West Province, South Africa [ 21 , 22 ]. The district is home to 1.5 million people; mining and agriculture are the major sources of revenue, with 40% of economically active adults unemployed [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Study enrollment occurred from October 2014 to April 2015 and follow-up continued through May 2016. At the time of the study, 1 in 5 adults in the province and nearly 1 in 3 pregnant women were living with HIV [ 22 , 26 , 27 ]. Bojanala District was not part of the 2014-2016 national pilot program for differentiated care interventions: HIV care was provided centrally within Department of Health primary care facilities [ 28 ].…”
Section: Methodsmentioning
confidence: 99%